1987
DOI: 10.1093/nar/15.23.9975
|View full text |Cite
|
Sign up to set email alerts
|

Thymine methyls and DNA–protein interactions

Abstract: Evidence is summarized showing that thymine methyls are as important in the recognition of specific sequences by proteins as are the more widely recognized hydrogen bonding sites of bases in the major groove (1). Strongest evidence has come from experiments using functional group mutagenesis (2) in which thymines in a specific recognition sequence (e.g., promoters, operators and restriction sites) are replaced by oligonucleotide synthesis with methyl-free uracil or cytosine and 5-methylcytosine. Such experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 38 publications
2
42
0
1
Order By: Relevance
“…We recently have shown that replacement of the hydrophobic 5-methyl group of thymine with the bulkier, hydrophilic 5-hydroxymethyl group, results in a significant decrease in binding of the ubiquitous transcription factor, AP-1 (15). Indeed, there are many sequence-specific DNA binding proteins that recognize the 5-methyl group of thymine in the major groove of DNA as a docking site (16), suggesting that HmU accumulation in DNA has great potential to disrupt gene regulation, and thus could be a main reason that multiple overlapping glycosylases exist to repair this lesion out of the DNA of human cells.…”
Section: Introductionmentioning
confidence: 99%
“…We recently have shown that replacement of the hydrophobic 5-methyl group of thymine with the bulkier, hydrophilic 5-hydroxymethyl group, results in a significant decrease in binding of the ubiquitous transcription factor, AP-1 (15). Indeed, there are many sequence-specific DNA binding proteins that recognize the 5-methyl group of thymine in the major groove of DNA as a docking site (16), suggesting that HmU accumulation in DNA has great potential to disrupt gene regulation, and thus could be a main reason that multiple overlapping glycosylases exist to repair this lesion out of the DNA of human cells.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for detecting contacts between thymines and proteins have been described (7,8). They involve either expensive synthesis of oligonucleotides and the use of base analogues that yield precise and reliable information about the importance of methyl groups of thymines (7) or hydrazine treatment of DNA that results in a complete removal of the thymine base and opening of the sugar ring (8).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are thymine residues conserved in both subgroups. In an attempt to study directly the participation of thymine residues within the HRE in specific binding of the hormone receptors, and in the discrimination between different HREs, we have searched for appropriate chemical procedures.Methods for detecting contacts between thymines and proteins have been described (7,8). They involve either expensive synthesis of oligonucleotides and the use of base analogues that yield precise and reliable information about the importance of methyl groups of thymines (7) or hydrazine treatment of DNA that results in a complete removal of the thymine base and opening of the sugar ring (8).…”
mentioning
confidence: 99%
“…Methyl groups were introduced at the 5 position of cytosine with the C-C bond length constrained to that previously determined in crystalline Z-DNA (23). As with thymine methyls, cytosine methyls are not expected to perturb B-DNA conformation, since both pyrimidine methyls occupy roughly the same position in the major groove of the B-DNA helix (24,25). This expectation was consistent with the molecular modeling carried out here, in which the energy-minimized structure was found to be roughly isomorphic to the B-DNA conformation adopted by the structure prior to minimization.…”
mentioning
confidence: 99%